'Art in Transit': A pedagogic approach. Issue 2 (1st June 2017) - Mistry, Arzu
This article shares the impetus, processes, dilemmas, and research of Art in Transit, a pedagogic project. The project is facilitated by faculty at the Srishti Institute of Art, Design and Technology, and focuses on contemporary art and design education and its relationship to place, in this case, Bangalore. The article details the research pursuits that stem from the challenges of praxis in situ, surfacing tensions that arise from engagement with communities, government agencies, education guidelines, and participating city, national and international artists. Projects by students and collaborating artists are shared as examples to illustrate and counter the binaries that emerge, for example, place and practice, or activism and gentrification. The project is framed within the worlds of Critical Pedagogy, Place-Based Education and Public Pedagogy.